Kajian Pemilihan Unit Bisnis Pemberi Jasa Layanan Internet Dengan Pendekatan Analitical Hierarchy Process (AHP) : Studi Kasus LP3I Jakarta Cabang Pondok Gede - Hesti Rian (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Internet facilities in every college has become indispensable in providing education to attract more prospective students. Intense competition universities both public and private in the competition, would require a strategic capable of winning the competition, the provision of internet facilities is one way to face such competition. Polytechnic LP3I Jakarta Pondok Gede branch is one of the private universities which are currently improving the quality of service. In addition to the attraction of new students to register, internet facilities are also urgently needed at the Polytechnic LP3I Jakarta Pondok Gede branch during the learning process. In an effort to achieve the goal Polytechnic LP3I Jakarta branch in Pondok Gede who formulated the vision and mission, the Polytechnic LP3I Jakarta branch of Pondok Gede try to provide the best facilities for its students is one of them by providing fast internet facilities by selecting a business unit of internet service providers accordingly. Study selection business unit of internet service providers are using the AHP approach (analytical Hierarchy Process) with the software Expert Choice 2000. The study is expected to generate an appropriate method in determining the business unit that Internet service providers suitable for use in Polytechnic LP3I Jakarta Pondok Gede branch to an increase in the provision of services to students.